JENDL/ImPACT-2018: a new nuclear data library for innovative studies on transmutation of long-lived fission products. Issue 12 (2nd December 2019) - Kunieda, Satoshi; Furutachi, Naoya; Minato, Futoshi; Iwamoto, Nobuyuki; Iwamoto, Osamu; Nakayama, Shinsuke; Ebata, Shuichiro; Yoshida, Toru; Nishihara, Kenji; Watanabe, Yukinobu; Niita, Koji
ABSTRACT: A new nuclear data library, JENDL/ImPACT-2018, was developed for an innovative study on the transmutation of long-lived fission products. Nuclear reaction cross-sections were newly evaluated for incident neutrons and protons up to 200 MeV for 163 nuclides focusing on long-lived nuclei such as 79 Se, 93 Zr, 107 Pd and 135 Cs, adopting some parts of JENDL-4.0. Our challenge was an evaluation of cross-sections for a number of unstable nuclei over a wide energy range where the experimental data were very scarce. We estimated cross-sections based on a nuclear model code CCONE by incorporating an advanced knowledge on the nuclear structure theory and a model-parameterization based on new experimental cross-sections measured by the inverse kinematics. Through comparisons with available experimental data on the stable isotopes, it is found that the present data give better agreements with them than those in the existing libraries. In a neutronics simulation by the PHITS code, we also found that the largest impact of the present library was seen on the estimated amount of isotope productions.